NSP4 and ORF9b of SARS-CoV-2 Induce Pro-Inflammatory Mitochondrial DNA Release in Inner Membrane-Derived Vesicles - Md Imam Faizan; Rituparna Chaudhuri; Shakti Sagar; Sarah Albogami; Nisha Chaudhary; Iqbal Azmi; Areej Akhtar; Syed Mansoor Ali; Rohit Kumar; Jawed Iqbal; Mohan C. Joshi; Gaurav Kharya; et al. (Cells, 2022)
Circulating cell-free mitochondrial DNA (cf-mtDNA) has been found in the plasma of severely ill COVID-19 patients and is now known as a strong predictor of mortality. However, the underlying mechanism of mtDNA release is unexplored. Here, we show a novel mechanism of SARS-CoV-2-mediated pro-inflammatory/pro-apoptotic mtDNA release and a rational therapeutic stem cell-based approach to mitigate these effects. We systematically screened the effects of 29 SARS-CoV-2 proteins on mitochondrial damage and cell death and found that NSP4 and ORF9b caused extensive mitochondrial structural changes, outer membrane macropore formation, and the release of inner membrane vesicles loaded with mtDNA. The macropore-forming ability of NSP4 was mediated through its interaction with BCL2 antagonist/killer (BAK), whereas ORF9b was found to inhibit the anti-apoptotic member of the BCL2 family protein myeloid cell leukemia-1 (MCL1) and induce inner membrane vesicle formation containing mtDNA. Knockdown of BAK and/or overexpression of MCL1 significantly reversed SARS-CoV-2-mediated mitochondrial damage. Therapeutically, we engineered human mesenchymal stem cells (MSCs) with a simultaneous knockdown of BAK and overexpression of MCL1 (MSCshBAK+MCL1) and named these cells IMAT-MSCs (intercellular mitochondrial transfer-assisted therapeutic MSCs). Upon co-culture with SARS-CoV-2-infected or NSP4/ORF9b-transduced airway epithelial cells, IMAT-MSCs displayed functional intercellular mitochondrial transfer (IMT) via tunneling nanotubes (TNTs). The mitochondrial donation by IMAT-MSCs attenuated the pro-inflammatory and pro-apoptotic mtDNA release from co-cultured epithelial cells. Our findings thus provide a new mechanistic basis for SARS-CoV-2-induced cell death and a novel therapeutic approach to engineering MSCs for the treatment of COVID-19.